2021
DOI: 10.3390/healthcare9050545
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Dyslipidemia and Factors Associated with Mortality in Schizophrenia: A Population-Based Study in Taiwan

Abstract: Background: Persons with schizophrenia are at greater risk of developing subsequent medical conditions. To date, few studies have examined comprehensively the risks, mortality and survival rates in schizophrenia and subsequent dyslipidemia over different time periods. The objective of this study was to evaluate the occurrence of subsequent dyslipidemia after the diagnosis of schizophrenia, and factors associated with mortality and survival rate in patients with schizophrenia. Methods: We used a population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A previous study reported a 2.9-fold higher risk of all-cause mortality in patients with schizophrenia compared to the general population, and a 1.6-fold higher risk compared to controls matched for physical diseases ( 36 ). Although several risk factors including cardiovascular diseases ( 37 ), stroke ( 37 , 38 ), smoking ( 39 ), physical fitness and inactivity ( 40 ), obesity ( 41 ), dyslipidemia ( 42 ), any cancer ( 43 ), and suicide ( 44 ) have been associated with all-cause mortality in patients with schizophrenia, the exact pathophysiological mechanisms have yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a 2.9-fold higher risk of all-cause mortality in patients with schizophrenia compared to the general population, and a 1.6-fold higher risk compared to controls matched for physical diseases ( 36 ). Although several risk factors including cardiovascular diseases ( 37 ), stroke ( 37 , 38 ), smoking ( 39 ), physical fitness and inactivity ( 40 ), obesity ( 41 ), dyslipidemia ( 42 ), any cancer ( 43 ), and suicide ( 44 ) have been associated with all-cause mortality in patients with schizophrenia, the exact pathophysiological mechanisms have yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%